Pancasila Values Were Forgotten In The Formation Of Indonesian Legislation - Supeno, Bambang Joyo; Widyorini, Sri Retno (PDIH Untag Semarang, 2024)
the ideology of the Indonesian nation, is considered to have been neglected in the formation of legislation. As is known, Pancasila, as the source of all sources of state law, is interpreted as the principles or foundation for thinking and acting in the formation and enforcement of legislation. Empirically, the values of Pancasila have been forgotten as principles, both in abstracto and in concreto, leading to deviations, disharmony, and inconsistency in the formation of legislation. This study is a qualitative research using a normative juridical approach, which will explore and analyze these issues using secondary data and purposive random sampling. The analysis results show that three factors influence the neglect of Pancasila values as